Childhood picky eating behaviour and its impact on the growth of young children: a scoping review - Ahmad Nazri, Nurshazwani; Jaafar, Nurul Hazirah; Suriati, Zakaria; Mohd Abu Bakar, Wan Azdie; Azahari, Nuraniza; Hisham, Syifak Izhar; Buhari, Siti Sabariah (IIUM Press, 2024)
Background: Malnutrition occurs due to inadequate food intake and low daily energy intake, often associated with picky eating behaviour (PEB). Picky eaters have limited food choices and poor dietary diversity, leading to malnutrition. Therefore, this article aims to explore the impact of childhood eating behaviour on a young child's growth. Method: Articles were identified through six electronic search engines using 12 keywords. Articles were included if they met the following criteria:(1) sample of study involved young children (below six years old); (2) study outcome focusing on the impact of eating behaviour on the growth of the children (3) published in English. Studies were excluded if they were review articles, qualitative studies, and involved children with clinical health problems. Result: A total of 413 articles were screened, and 8 full-text articles were evaluated. The prevalence rates of selective eaters varied greatly from 25% in India to 77% in Iraq. The screening tools used for identifying PEBvaried, with the Children’s Eating Behaviour Questionnaire (CEBQ) being the most commonly used tool. Short-term implications of PEB on children include the risk of poor diet intake and limited consumption of a variety of food groups, which can lead to adverse health outcomes. Meanwhile, long-term implications include the development of eating disorders in adulthood. Conclusion: Our findings reveal that PEB has had a significant impact on the growth of young children. Despite the increasing concern about the implications of PEB, there is a lack of sufficient research studies on the effects of this behaviour on the nutritional status of young children